2021
DOI: 10.1002/cbdv.202100207
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Fingerprints and Bioactivities of Ripe Disseminules (Fruit‐Seeds) of Seventeen Gundelia (Kenger‐Kereng Dikeni) Species from Anatolia with Chemometric Approach

Abstract: Gundelia species are known as “Kenger‐kereng dikeni” in Anatolia, and their aerial parts are consumed as food. Also, roots and seeds (disseminules) of the Gundelia species are used to prepare gum and coffee. The chemical contents of ethanol and hexane extracts of disseminules of 17 Gundelia species, 13 of them are endemic, were studied using LC/MS/MS and GC/MS. Additionally, their antioxidant potential and enzyme inhibitory capacity against acetyl‐ and butyryl‐cholinesterase, urease, and tyrosinase were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, the model showed two peaks with positive regression As the complexity of herbal extracts often makes it often difficult to purify bioactive compounds within a reasonable time limit, the use of a combination of LC fingerprinting and chemometrics has gained in popularity in recent years as an efficient method to identify metabolites potentially responsible for a given biological activity (Ben Ahmed et al, 2022;Ertas et al, 2021).…”
Section: Identification Of Potential Anti-ache And/or Anti-buche Meta...mentioning
confidence: 99%
“…In addition, the model showed two peaks with positive regression As the complexity of herbal extracts often makes it often difficult to purify bioactive compounds within a reasonable time limit, the use of a combination of LC fingerprinting and chemometrics has gained in popularity in recent years as an efficient method to identify metabolites potentially responsible for a given biological activity (Ben Ahmed et al, 2022;Ertas et al, 2021).…”
Section: Identification Of Potential Anti-ache And/or Anti-buche Meta...mentioning
confidence: 99%
“…For determination of these phytochemicals, LC/MS/MS had a great importance. This technique has effective analytical separation, precise measurements and reliable results even at low concentrations [10] …”
Section: Introductionmentioning
confidence: 99%
“…This technique has effective analytical separation, precise measurements and reliable results even at low concentrations. [10] Recent studies have shown that antioxidants cause metabolic improvement in many diseases. Like antioxidants, enzyme inhibitors show similar properties and good health effects in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…Different phenolic compounds‐from simple phenolic acids to flavonoid aglycones and glycosides‐have different sizes and polarities, which can make it challenging to extract and analyze them. The needs of selectivity, separation efficiency, and sensitivity should be satisfied by analytical techniques employed to identify natural compounds in medicinal and aromatic plants [7,8] . Therefore, tandem mass spectrometry (MS/MS) combined with ultra‐high performance liquid chromatography (U‐HPLC) is one of the best methods for qualitative and quantitative characterization and identification of different types of phenolic compounds in different plant species [9,10] …”
Section: Introductionmentioning
confidence: 99%
“…The needs of selectivity, separation efficiency, and sensitivity should be satisfied by analytical techniques employed to identify natural compounds in medicinal and aromatic plants. [7,8] Therefore, tandem mass spectrometry (MS/MS) combined with ultrahigh performance liquid chromatography (U-HPLC) is one of the best methods for qualitative and quantitative character-ization and identification of different types of phenolic compounds in different plant species. [9,10] Campanula L., is the largest genus of the Campanulaceae and is represented around 420 species worldwide.…”
Section: Introductionmentioning
confidence: 99%